Diaportones A–C: Three New Metabolites From Endophytic Fungus Diaporthe foeniculina BZM-15 - Kang, Fenghua; Lu, Xiuxiang; Zhang, Sha; Chen, Dekun; Kuang, Min; Peng, Weiwei; Tan, Jianbing; Xu, Kangping; Zou, Zhenxing; Tan, Haibo (Frontiers in Chemistry, 2021)
Phytochemical investigation of Diaporthe foeniculina BZM-15 led to one new γ-butyrolactone derivative, diaportone A (1), one cyclopentenone derivative, diaportone B (3), one monoterpene, diaportone C (5), along with six known compounds (2, 4, and 6-9). By means of NMR, HRMS, ECD spectroscopy and quantum chemistry calculation, all chemical structures as well as the absolute configurations for the new compounds were elucidated. Furthermore, all compounds were evaluated for their cytotoxic activity and antibacterial activity, and compounds 7 and 8 displayed significant anti-proliferative effects to three human cancer cell lines (SF-268, MCF-7 and HepG2) with IC50 values ranging from 3.6 to 15.8 μM.